Implementasi Pembelajaran Aqidah Akhlak Terhadap Pembentukan Karakter Siswa di MTsN 5 Karawang - Rifki Junaedi; Ari Prasetyo (Mujalasat: Multidiciplinary Journal of Islamic Studies, 2024)
This research explains the implementation of character education through Aqidah Akhlak lessons at MTsN 5 Karawang. The research aims to identify the challenges faced by teachers in integrating character education and to provide an overview of the planning, execution, and evaluation conducted by Aqidah Akhlak instructors. The research methodology involves observation, interviews, and document analysis, using a qualitative approach. The research findings indicate the following: 1) Aqidah Akhlak Learning Planning: Despite efforts to integrate character education into Aqidah Akhlak lesson planning, the planning still tends to focus more on characterization rather than being at the core of the learning plan. 2) Conventional Implementation: Findings show that character education in the Aqidah Akhlak subject follows conventional teaching patterns, with limited relevant connections between character instruction and the subject matter. 3) Limited Evaluation Techniques: Character assessments rely solely on observational methods. There is a need to develop a more comprehensive evaluation approach that encompasses various techniques to gain a better understanding of students' character development.